Visual Thumbnail Komik Digital “Merah Di Langit Bandung” - Salsabila, Olivia; Daniar, Aninditya; Wulandari, Sri (Besaung : Jurnal Seni Desain dan Budaya, 2025)
The digital comic Merah di Langit Bandung tells the heroic story of Mohammad Toha and Mohammad Ramdan during the historic Bandung Sea of Fire event, focusing on their high-risk mission to detonate the Dutch munitions warehouse in Dayeuhkolot in 1946. Featuring rich historical elements, this comic aims to reintroduce the nation's struggle for independence to younger generations in a more modern and accessible format. Consequently, Merah di Langit Bandung is published on LINE Webtoon, a popular platform for online comic reading that offers high accessibility and convenience for readers. This platform allows for dynamic storytelling and powerful visuals, making it highly relevant to the preferences of today's generation. Research for this project employed both quantitative and qualitative methods to understand audience needs and interests. One key aspect of the comic’s development is the thumbnail design, which not only serves as a visual representation of the story but also acts as an initial attraction that can make readers pause and decide to explore further. An effective thumbnail can be a deciding factor in capturing readers’ attention amid a vast array of available comics. Data analysis and surveys conducted with the target audience provided insights into the most effective visual elements, resulting in a captivating design concept. The proposed thumbnail design alternatives were chosen based on audience preferences, with the hope that the final design will maximize this digital comic’s appeal to readers.